2010
DOI: 10.14710/jitaa.35.2.129-133
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF KAPOK (Ceiba pentandra) SEED OIL SUPPLEMENTATION ON CELLULOLYTIC ENZYME AND RUMEN MICROBIAL FERMENTATION ACTIVITY OF LOCAL SHEEP

Abstract: This research was conducted to study the influence of kapok seed oil (KSO) supplementation on cellulolytic enzyme and microbial fermentation activity. Sheep rumen fluid was used as enzyme source and inoculant, whereas carboxymethylcellulose (CMC) was used as the substrate. There were 4 levels of KSO supplementation as treatment, i.e. : 0% (T0), 5% (T1), 10% (T2), and 15% (T3). Two measured variables were reduced sugar production rate and gas fermentation production. The data were analyzed by analysis of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Supplementation of 5% palm oil increased the growth and efficiency of feed conversion in weaning lamb (Dutta et al, 2008). Meanwhile, kapok seed oil (up to 5%) supplemented to sheep did not affect the cellulolytic enzyme activity in the rumen (Widiyanto et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Supplementation of 5% palm oil increased the growth and efficiency of feed conversion in weaning lamb (Dutta et al, 2008). Meanwhile, kapok seed oil (up to 5%) supplemented to sheep did not affect the cellulolytic enzyme activity in the rumen (Widiyanto et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Treatment factor I was KSO supplementation, consisting of two levels, namely, K 0 (without supplementation) and K1 (protected KSO supplementation) with supplementation levels of 10% dry matter (DM) rations and 75% protection level, based on the results of research by Widiyanto et al . [ 6 ]. Treatment factor II was CC supplementation, consisting of three levels, namely, C0 (0%), C 1 (1.5%), and K 2 (0.3%), based on the DM of feed.…”
Section: Methodsmentioning
confidence: 99%
“…As an illustration, the research of Widiyanto et al . [ 2 ] showed that supplementation with 10% kapok seed oil (KSO) with a protection level of 75% in the ration of thin-tailed sheep resulted in a decrease in cholesterol levels of thin-tailed sheep meat from 89.21 mg to 62.46 mg/100 g and an increase in the relative proportion of omega-6 fatty acids from 3.68% to 15.52%. The weight gain of sheep increased from an average of 62 g/day–99 g/day.…”
Section: Introductionmentioning
confidence: 99%